PROTECTION OF CHILDREN'S RIGHTS AND WOMEN'S RIGHTS AS PART OF HUMAN RIGHTS IN INDONESIA THROUGH RATIFICATION OF INTERNATIONAL REGULATIONS - Failin Failin; Anny Yuserlina; Eviandi Ibrahim (Jurnal Cendekia Hukum, 2022)
Protection of human rights, regardless of age and gender, everyone has the right to protection. Indonesia as a state of law is obliged to protect the human rights of its people, and joining Indonesia as a member of the United Nations requires it to ratify regulations relating to the protection of children and women. This article will discuss the extent of ratification by the Government of Indonesia to promote the protection of children's rights and women's rights. This type of legal research is also commonly referred to as doctrinal legal research or library research. It is called doctrinal legal research because this research is only aimed at written regulations so that this research is very closely related to libraries because it will require secondary data in the library. The results of the study show that the Government of Indonesia has advanced the protection of children's rights with the ratification of the Convention on the Rights of the Child in the Presidential Decree of the Republic of Indonesia Number 36 of 1990, besides that it also gave birth to the Child Protection Law. As for the protection of women, in 1984 Indonesia ratified the Convention on the Elimination of All Forms of Discrimination Against Women through Law Number 7 of 1984 concerning Ratification of the Convention on the Elimination of All Forms of Discrimination Against Women, which was then followed by Presidential Instruction Number 9 of 2000 concerning Gender Mainstreaming and Law Number 23 of 2004 concerning the Elimination of Domestic Violence, so that the protection of women in Indonesia is more protected.